2013
DOI: 10.1007/s11434-013-5958-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of two phosphohexomutase genes in glycogen synthesis in Synechocystis sp. PCC6803

Abstract: Phosphohexomutases catalyze the interconversion between hexose-6-phosphate and hexose-1-phosphate and play important roles in polysaccharide synthesis. In Synechocystis sp. PCC 6803, sll0726 is predicted to encode PGM (phosphoglucomutase), slr1334 is predicted to encode a PGM/PMM (phosphomannomutase) bifunction enzyme. In comparison to the wild type, a sll0726-null mutant showed 3.4% PGM activity but 45%-69% glycogen content. Down-regulation of slr1334, an essential gene, by using a copper regulated promoter f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…This has in fact been shown for PNGM from E. coli which is considered to be an essential enzyme 22 . This makes the role of Glc-1,6-BP in carbon metabolism even more relevant and would explain the failure in deleting the slr1334 gene shown by 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has in fact been shown for PNGM from E. coli which is considered to be an essential enzyme 22 . This makes the role of Glc-1,6-BP in carbon metabolism even more relevant and would explain the failure in deleting the slr1334 gene shown by 17 .…”
Section: Discussionmentioning
confidence: 99%
“…While Sll0726 exhibits typical properties of PGMs [14][15][16] , little is known about Slr1334. The only study addressing this issue reported that purified Synechocystis Sll0726 has about a tenfold higher activity in vitro than Slr1334 and that a sll0726 knockout mutant only shows around 3 % PGM activity compared to the wildtype 17 . Despite its low contribution to over-all PGM activity, the Slr1334 product appeared to be essential as it was not possible to acquire fully segregated knockout mutants of the slr1334 gene, which raised the question of the role of Slr1334 in Synechocystis.…”
Section: Introductionmentioning
confidence: 99%
“…6-phosphogluconate dehydrogenase was assayed in 10 mM MgCl 2 and 50 mM Tris maleate, pH 7.5 with 2 mM NADP + and 2 mM 6-phosphogluconate (Sigma-Aldrich) as substrate ( Schaeffer and Stanier, 1978 ). Phosphoglucomutase was assayed in 50 mM Tris-HCl, pH 8.0 and 10 mM DTT with 2 mM MgCl 2 , 10 μM glucose-1,6-bisphosphate, 1 mM NADP + , 0.2 U ml −1 glucose-6-phosphate dehydrogenase and 2 mM glucose-1-phosphate (Sigma-Aldrich) as substrate ( Liu et al, 2013 ). Glycogen synthase was assayed in a three-step reaction following Suzuki et al (2010) .…”
Section: Methodsmentioning
confidence: 99%
“…8,9 Although Synechocystis possesses two Pgm isoenzymes, Pgm1 (sll0726) has been shown to be responsible for almost 97 % of the Pgm activity. 10 Pgm1 was recently identified as a phosphoprotein with two localized serine phosphorylation sites: Ser 63 and Ser 68. Ser 168, which is predicted to be in the catalytic center, shows diminished phosphorylation during chlorosis.…”
Section: Introductionmentioning
confidence: 99%
“…An exception to the abundance pattern of most glycogen catabolic enzymes is PGM1, the expression of which is suppressed under nitrogen starvation and activated during resuscitation. 8,9 Although Synechocystis possesses two PGM isoenzymes, PGM1 ( sll0726 ) has been shown to be responsible for almost 97 % of the PGM activity, 10 while PGM2 ( slr1334 ) serves as glucose-1,6-bisphosphate synthase. 11 PGM1 was recently identified as a phosphoprotein with two localized serine phosphorylation sites: Ser 47 and Ser 152.…”
Section: Introductionmentioning
confidence: 99%